A Comparative Study on the Attitudes and uses of Music by Adults with Visual Impairments and those who are Sighted. (July 2015) - Park, Hye Young; Chong, Hyun Ju; Kim, Soo Ji
Introduction: This study investigated attitudes (intrapersonal, interpersonal, and communal) toward, and uses of, music among people with visual impairments compared with those who are sighted to investigate the potential of music as a means of communication and social expression. Method: A total of 137 participants (63 visually impaired, 74 sighted) were recruited from six cities in South Korea. Participants, aged 20 to 39 years, were asked to complete a 30-question survey on music attitudes and use, which was distributed (electronically, by post, by telephone, and in person) between June 2013 and February 2014. Results: The response rate was 87%. Attitudes toward music showed that visually impaired participants demonstrated significantly higher (more positive) values than sighted participants on interpersonal and communal survey dimensions ( p < .05). The groups demonstrated similar results regarding intrapersonal attitudes, which received the highest scores of all three categories. Visually impaired participants mainly accessed music from home via portable devices or computers, whereas sighted participants used music most frequently at their homes or in cars. The most significant difference between groups was that music was involved in the majority of leisure time for visually impaired participants, but not for sighted participants. Discussion: Higher attitude scores in the intrapersonal category from both groups imply an important role of music, with its emotional and affective aspects, in self-expression. Findings indicated that visually impaired participants utilized music mainly for self-amusement despite perceiving it as an interpersonal and communal tool, most likely due to social restrictions. Implications for practitioners: The role of music in the lives of visually impaired individuals could be expanded to provide more group opportunities, hands-on experiences, enjoyable outdoor activities, and psychosocial coping strategies. Group music programs should be considered in order to expand interpersonal and communal experiences for both visually impaired and sighted individuals.